دراسة أثر مؤشرات البنية التحتية على النمو الاقتصادي في سورية - أحمد, طالب; ديب, مازن (Latakia University Journal - Economic and Legal Sciences Series, 2016)
Quality and quantity of national economic infrastructure are significantly related to economic growth in medium and long terms. Infrastructure is considered as the motive of economic activities. Besides, it establishes an environment for production activities and makes growth easier.In this research, we followed the analytical descriptive method and studied the development of some of infrastructure indicators(Asphalted Roads lengths, amount of goods transferred by trains, quantity of water productivity, quantity of electricity, a number of phone lines, a number of schools, a number of hospitals, and a number of health centers) through the period( 1995- 2010) by reducing infrastructure indicators with factor analysis method, and we got one virtual factor, and studied the relationship between the growth of domestic products as an indicator of economic growth and the actor factor to infrastructure indicators that chosen for this study targets(single- handed) in study period, The research obtains suitable standard liner models for the relations, that emphasis on powerful relationship between infrastructure & economic growth and that can be depended on in the future to plan the infrastructure.إنّ كمية وجودة البنية التحتية الوطنية الاقتصادية لها علاقة مهمّة بالنمو الاقتصادي على المدى المتوسط وطويل الأجل, حيث ينظر للبنية التحتية غالباً على أنها محرك للنشاط الاقتصادي, وتكوّن بيئة للأنشطة الانتاجية وتسهّل النمو.وفي هذا البحث اتبعنا المنهج الوصفي التحليلي ودرسنا تطور بعض مؤشرات البنية التحتية (أطوال الطرق الاسفلتية, كمية البضائع المنقولة عبر السكك الحديدية, كمية المياه المنتجة, كمية الكهرباء المولدة, عدد الخطوط الهاتفية, عدد المدارس, عدد المستشفيات, عدد المراكز الصحية) خلال الفترة (1995-2010) من خلال اختزال مؤشرات البنية التحتية باستخدام طريقة التحليل العاملي حيث توصلنا إلى عامل فرضي واحد, ودراسة تحليل الانحدار للعلاقة بين الناتج المحلي الاجمالي كمؤشر للنّمو الاقتصادي والعامل الممثل لمؤشرات البنية التحتية خلال الفترة المدروسة, حيث توصلنا نتيجة لذلك الى الحصول على نموذج رياضي خطي يؤكّد قوّة العلاقة بين البنية التحتيّة والنمو الاقتصادي وبالتالي يمكن الاعتماد عليه مستقبلاً في تخطيط البنية التحتية.